The Influence of Immersion Duration and Organic Growing Organics on Sugar Cane (Saccharum omcinarum L) Growth and Yield - Fauziatun Nisak; Yeni Ika Pratiwi; Mahrus Ali (Agricultural Science, 2017)
The purpose of this research is to determine the influence of interaction between organic growth regulator concentration and immersion duration time, as well as the influence of each of these factors on germination sugarcane (Saccharum officinarum L)cuttings. This study uses a randomized group design (RAK) with two factors, immersion duration (P)in 4 levels of P1 (1 minute), P2 (2 min), P 3 (3minutes), and P4 (4 minutes) and two levels of organic plant growth regulator (K), 4 cc/ liter, and 5 cc per liter of water, each treatment is repeated 3 times to obtain 24 treatments. The results reveals that a)There is a significant interaction effect due to immersion duration and concentrations of organic growth regulator to the observed variables: number of roots per plant, root length per plant, gross weight per plant and net weight per plant at the end of the observation b). Each factor of both immersion and concentration of organic plant growth provide significant influence on all the variables studied. 0). The highest value on all the variables observed is achieved by K2P4 treatment with concentration of 5 cc/liter and 4 minutes immersion; yet statistically, the optimum value is achieved by treatment K2P3 or influence of K2 and P3treatment.